2006
DOI: 10.1099/mic.0.28489-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hydrolysis of S-adenosylmethionine induces the met regulon of Escherichia coli

Abstract: Regulation of methionine biosynthesis in Escherichia coli involves a complex of the MetJ aporepressor protein and S-adenosylmethionine (SAM) repressing expression of most genes in the met regulon. To test the role of SAM in the regulation of met genes directly, SAM pools were depleted by the in vivo expression of the cloned plasmid vector-based coliphage T3 SAM hydrolase (SAMase) gene. Cultures with in vivo SAMase activity were assayed for expression of the metA, B, C, E, F, H, J, K and R genes in cells grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…It is clear that in minimal medium, addition of SAM is insufficient, and only one other metabolite, methionine, is required by a SAM synthase deficient strain. This is consistent with the fact that expression from all the promoters of the methionine biosynthetic genes is repressed by SAM and MetJ (Lawrence et al, 1968;LaMonte & Hughes, 2006) so that an adequate supply of methionine cannot be synthesized in the presence of SAM.…”
Section: Resultssupporting
confidence: 61%
“…It is clear that in minimal medium, addition of SAM is insufficient, and only one other metabolite, methionine, is required by a SAM synthase deficient strain. This is consistent with the fact that expression from all the promoters of the methionine biosynthetic genes is repressed by SAM and MetJ (Lawrence et al, 1968;LaMonte & Hughes, 2006) so that an adequate supply of methionine cannot be synthesized in the presence of SAM.…”
Section: Resultssupporting
confidence: 61%
“…These results indicated that MetJ regulates the levels of both MetE and MetR, and suggested that a shortage of SAM through MetK dysfunction in GroE-depleted cells increases the levels of the activator MetR. A similar overexpression of MetR has been observed when SAM is depleted through the strong SAM hydrolase of a phage (LaMonte & Hughes, 2006). Since the metE promoter is regulated by MetR and UuMetK suppresses overexpression of the metE promoter lacking MetJ-binding regions, it is plausible that the increased level of MetR contributes to the overexpression of MetE in GroE-depleted cells.…”
Section: Activation Of the Metr Promoter In Groe-depleted Cellssupporting
confidence: 51%
“…Reporter assays and suppression by UuMetK suggested that the increased expression of MetR in GroE-depleted cells contributes substantially to the overexpression of MetE, as has been suggested elsewhere (LaMonte & Hughes, 2006). Accumulation of the MetR co-activator homocysteine caused by MetF dysfunction contributed little to the overexpression of MetE (Table 2).…”
Section: Regionmentioning
confidence: 76%
“…SAM is another likely AMC metabolite that is known to influence numerous phenotypic traits (19), as it has a number of fates within the cell (15,16,27 Thus, it is apparent that affecting levels of AMC metabolites may result in more global deregulated metabolism, which in turn could contribute to the growth defects observed. Accordingly, the current metabolite analysis did not identify a definitive mechanism that explains the changes observed.…”
Section: Discussionmentioning
confidence: 99%